2022
DOI: 10.1111/ecc.13688
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported practices, competence and difficulties towards palliative care among nurses: A cross‐sectional study

Abstract: Objective: Nurses' palliative care practice ability is the key to evaluating the quality of palliative care. This study aimed to identify the current situation of palliative care practices, competence and difficulties among nurses and determine whether difficulties play a mediating role between practices and competence.Methods: A cross-sectional study was conducted. The online survey comprised demographics, the Palliative Care Self-Reported Practices Scale, the Palliative Care Nursing Self-competence Scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Stoevelaar et al showed that a simplified RSL (four items) can also predict delirium without compromising on predictive accuracy (Stoevelaar et al, 2022). Van competencies and problem-solving abilities in palliative care are associated with their palliative care practices (An et al, 2022). Moreover, also Temiz et al conducted a survey study of 106 nurses working in hospitals in Turkey to assess their level of knowledge.…”
Section: How Can We Overcome These Barriers?mentioning
confidence: 99%
See 1 more Smart Citation
“…Stoevelaar et al showed that a simplified RSL (four items) can also predict delirium without compromising on predictive accuracy (Stoevelaar et al, 2022). Van competencies and problem-solving abilities in palliative care are associated with their palliative care practices (An et al, 2022). Moreover, also Temiz et al conducted a survey study of 106 nurses working in hospitals in Turkey to assess their level of knowledge.…”
Section: How Can We Overcome These Barriers?mentioning
confidence: 99%
“…An et al also recognised the importance of continuous education of healthcare professionals regarding palliative care. Based on a survey of 284 nurses, they conclude that nurses' competencies and problem‐solving abilities in palliative care are associated with their palliative care practices (An et al, 2022). Moreover, also Temiz et al conducted a survey study of 106 nurses working in hospitals in Turkey to assess their level of knowledge.…”
mentioning
confidence: 99%